Elemental profiling and determination of Ti content of the beach sand samples of Bangladesh using LIBS technique - Haider, A F M Yusuf; Wahadoszamen, Md; Sadat, M. E.; Abedin, Kazi Monowar; Talukder, A.I. (© 2010 Elsevier Ltd., 2017)
This article was published in the journal Optics and Laser Technology [© 2010 Elsevier Ltd.] and the definite version is available at : 10.1016/j.optlastec.2010.01.017